2005
DOI: 10.1097/01.psy.0000160476.67536.41
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress Preceding Idiopathic Ventricular Fibrillation

Abstract: These data suggest that psychosocial stress is playing a role in otherwise unexplained cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 30 publications
0
23
1
1
Order By: Relevance
“…However, overstimulated SGK activity may be detrimental. For example, it has been reported that psychosocial stress plays a role in otherwise unexplained cardiac arrest (39). Furthermore, a gain-of-function SGK1 mutation has been reported in twins who displayed the shortened QT interval, which induces arrhythmias and sudden death (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, overstimulated SGK activity may be detrimental. For example, it has been reported that psychosocial stress plays a role in otherwise unexplained cardiac arrest (39). Furthermore, a gain-of-function SGK1 mutation has been reported in twins who displayed the shortened QT interval, which induces arrhythmias and sudden death (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…It is at these brainstem and subcortical levels that central cardio-cardiac reflexes may exacerbate pathological autonomic responses to emotional challenges in cardiological patients placing them at risk of arrhythmia and sudden death (1,6,9). Beyond these brainstem centers, homoeostatic afferent information is conveyed by both basal and posterior ventromedial thalamic nuclei to the superior margin of the insula cortex, which supports a cortical representation of visceral state (9, 34, 37-42).…”
Section: Discussionmentioning
confidence: 99%
“…afferent homeostatic feedback ͉ electroencephalography ͉ heart beat-evoked potential ͉ insula cortex ͉ ischemia E motional events and mental stress can precipitate cardiac arrhythmia and sudden death in patients with heart disease (1-4). Electrocardiographic (ECG) indices of proarrhythmic electrical instability of the myocardium accompany psychological stress (5) and are associated with abnormalities in regional brain activity, suggesting abnormal efferent autonomic drive to the heart (1,6). Although a central efferent mechanism for arrhythmogenesis may also explain sudden death in disorders such as epilepsy (4,7), disturbances in cardiac afferent feedback may induce cardiogenic reflexes that enhance the vulnerability of cardiovascular disease patients to stress-induced arrhythmia (8).…”
mentioning
confidence: 99%
“…In the sample studied by Chandra et al (1988, as cited in Carvalho-Filho, 2000, the prevalence was 93.2%, both for ventricular arrhythmias as well as supraventricular arrhythmias. However, age is only a risk factor for coronary diseases when over 65 years, though not for idiopathic arrhythmias, as demonstrated in the study of Lane et al (2005). These authors found that patients with idiopathic ventricular fibrillation were significantly younger (36.0  11.6 years) than patients with coronary disease (57.1  8.1 years).…”
mentioning
confidence: 48%